Možnosti uporabe trdih prevlek na preoblikovalnih orodjih - Podgornik, Bojan (Strojniški vestnik, 2004)
The aim of this paper was to investigate the potential of using hard physical vapour deposition (PVD) coatings on forming tools. A tribological evaluation of TiN, TiB2, TaC and diamond like coating (DLC) coatings deposited on cold-worked tool steel was carried out in a load-scanning test rig and compared to the behaviour of different uncoated forming tool steels. The special test configuration, where austenitic stainless steel was used as the counter-material, makes it possible to gradually increase the normal load during forward sliding strokes, and to correspondingly decrease the load during reversed ones. In this investigation, the load range was 100 to 1300 N (contact pressure from 1 to 5 GPa). The experimental results indicate that theintroduction of an appropriate hard coating will lead to an improved wear resistance and a longer lifetime for the forming tool. Furthermore, by using hard low-friction coatings excellent anti-sticking properties can be obtained.
Keywords: preoblikovanje hladno; prevleke trde; adhezija; obraba; trenje; orodna jekla; tribologija; trde prevleke; hladno preoblikovanje